THE RELATIONSHIP BETWEEN EDUCATIONAL PROFILE, LEVEL OF CAREER INDECISION AND OF PERCEIVED SELF-EFFICACY REGARDING THE CAREER DECISION-MAKING PROCESS AMONG ADOLESCENTS - CLAUDIA CRIȘAN; SEBASTIAN TURDA (Studia Universitatis Babes-Bolyai, 2015)
ABSTRACT. Career indecision represents one of the key aspects in the field of vocational psychology. The present study, with a correlational design, aims to investigate the relationship between educational profile, the level of career indecision and the career decision-making self-efficacy among the late adolescents (N=160). The results showed that there is a significant positive correlation between career decision-making self-efficacy and students' educational profile, which means that there is a moderate association among these variables.